Synthesis of Research Theses in Music in Thailand During 2005 – 2014 - Boonyam, Treetip (Humanities, Arts and Social Sciences Studies, 2017)
The present research was aimed at providing a synthesis of research theses in music during 2005-2014 as well as a synthesis on research procedures of research theses that employed quantitative and qualitative methodologies and a summary of knowledge from various these containing both theories and essential contents from those studies by quantitative and qualitative music research synthesis. The data synthesis was carried out in the form of basic statistics and content analysis. The study found a total of 218 theses and dissertations from seven leading academic institutions in the ThaiLIS Database. Of these, 164 were qualitative studies and 54 were quantitative studies. The study found that there were few quantitative thesis dissertations on music during the aforementioned period and that most were qualitative researches. The quantitative research theses used more descriptive statistics in the data analysis than inferential statistics; therefore, these studies presented data that obtained from the sample group rather than the usage benefits of generalizations, which was the main purpose of quantitative research. In addition, the majority of research outcomes appeared in the form of exercise units or practices, so the research outcomes were rather non-diverse. For qualitative research, meanwhile, there existed outstanding characteristics on the aspect of diversity of content provided, which were focused on local music cultures and thereby demonstrated very clearly the heritages of ASEAN.